Rectangular Printed Antenna for 5G Mobile Communications With DGS - Zahra, Moussa Fatima; Ferouani, Souheyla; Yamina, Belhadef; Ghouti, Abdellaoui (Journal of Informatics and Mathematical Sciences, 2022)
Mobile communication systems are becoming more and more developed and the demand for services and throughput is in increasing. In our work, we designed a rectangular planar antenna for 5G at 3.5 GHz between 3.4-3.8 GHz. FR4 \((ε r=4.3\), \(h=1.5\) mm\()\) is used as material substrate. We used DGS to ameliorate the bandwidth of the rectangular antenna. Simulation results are very satisfactory in terms of S11, VSWR, Gain, and radiation pattern. The designed antenna is low-cost and easy for integrating to operate at 5G.